The South China piece in the Rodinian puzzle: A reply to the comment by Munteanu and Wilson - Li, Zheng-Xiang; Li, X.; Wang, Xuan-ce (Elsevier Science BV, 2009)
Uncritical application of geochemical plots for granitic rocks, without full appreciation of the limitations of such plots, the broader geological constraints and information about coexisting other rock types, commonly lead to incorrect tectonic interpretations. We consider this to be the case for the arc interpretations of the 850-740Ma igneous rocks in South China. In this Reply, we counter-argue all four lines of evidence used by Munteanu and Wilson [Munteanu, M., Wilson, A., this volume]. The South China piece in the Rodinian puzzle. A comment on "Assembly, configuration, and break-up history of Rodinia: a synthesis" by Li et al. (2008) [Precambrian Res. 160 (2008) 179-210]. Precambrian Res.] for an arc model in the western South China Block between 850 and 740 Ma.